Kongemagt og leding i Norge og Danmark omkring 1100 belyst ud fra den tidlige kristne fyrstedigtning - Malmros, Rikke (Historisk Tidsskrift, 2013)
Royal Power and Navy in Norway and Denmark about 1100 Elucidated by Early Christian Skaldic Court-Poetry(1) This study is an argument against a traditional view on eleventh century Danish society based on the work of C.F. Allen 1840: He argues that society in Nordic ’Antiquity’ consisted of common freemen who owned their farms, of ’magnates’ who were private owners of larger estates, and of the king who was the largest private landowner of all. No taxes were exacted and there was no hereditary nobility. In civil life there was no organisational bond between the king and individual members of society, every man in time of peace enjoying absolute freedom from public exactions. However, Allen’s view is not supported by contemporary sources. (2) Eleventh century Old Norse Christian court poetry continues the secular view of the tenth century pagan skalds: the king is the summit of a military pyramid, ’the army of the land’ (Malmros, Historisk Tidsskrift 1999). The change of religion AD 1000 makes the skalds diminish their use of pagan imagery leaving room for precise observations of time, people, and places. The Christian God is modelled on the terrestrial king, and vice-versa. (3) To the skalds the magnates constitute an aristocracy of birth. Magnates of good birth and with established local power serve as local officers to the overlords of Norway. (4) Eleventh century skalds have a wide vocabulary describing the free commoners who constitute the lið allra manna, the army of all men: most often they are called búendr. These are described as armed farmers mustered by both parts in civil war, trying to defend their land against invasions, and having sometimes their houses burned by foreigners or royal punitive expeditions. At the same time they are seen as the courageous menn, the þegnar, the vassals of the king (The Old Norse þegn being less exalted in society than his Anglo-Saxon counterpart þegen, þane). In spite of being viewed as the king’s men, the búendr when angered may gather at the þing planning rebellion. Here the búendr constitute a serious threat to the king and his officers. (5) The navy, the lið or leiðangr is mustered and led by the king. The jarlar, earls fight in the navy, its officers are called the vinir hilmis, the friends of the king, its rank and file being the búendr. In one stanza the leiðangr is called almenningr, the right and duty of all (free) men. The protection of the land, landvörn, is particularly seen as the task of the king and the magnates. The king musters the leiðangr and conducts a húsþing, a council of war before leaving, leads the cruise in foreign waters and gives the men heimför, home-leave at the end of the expedition. In 1064 the king of Denmark conducts a meeting of reconciliation with his Norwegian counterpart, followed by a lið allra Dana, an army of all Danes consisting of his valiant búendr. This is the only time Danish búendr are so named in skaldic poetry. (6) The men of the official leiðangr led by the king into foreign parts may be termed víkingar when praised by the skalds, just as the men of minor plundering bands are hailed as víkingar. But to the king ruling his home-country víkingar are a menace, duly punished by hanging. It is the duty of the king to uphold the law and the peace by draconic punishments. Just after his death AD 1103 King Eric the Ever-Good of Denmark is praised as upholding lög goðs, the law of God. (7) Adam of Bremen tells us that his contemporary, king Sven Estrithson of Denmark (1047-76) swore allegiance to Magnus the Good of Norway becoming his homo, his vassal. This is well attested by the skalds of the Norwegian king calling Sven jarl. In spite of any oath of allegiance the warfare between king and jarl goes on incessantly. This reminds us of relations in contemporary Frankish and Anglo-Saxon societies, the kings trying to maintain a precarious hold on their realms by personal bonds and ’clienteles’ without being able to have their God given offices respected. (8) Adam of Bremen also relates that Sven Estrithson receives tributum from ships preparing to go on viking raids against the pagans of the Baltic. (9) 1078 Pope Gregory VII writes to the king of Norway on the assumption that the king of Denmark (Harald Hen) can give bona et honores to his recalcitrant but politically important brothers by taking these sources of income back from his own friends. (10) A charter of May 21 AD 1085 by king Canute IV (later termed the ’Saint’) is witnessed by a dux and numerous stabularii, certainly magnates in official positions and in the service of the king. In this letter Canute maintains his right to fine peasants who neglect service to the expeditio. (11) An early work on the martyrdom 1086 of Canute, Passio sancti Canuti Regis et Martiris (1095) says that the navy is levied by the king and the principes in unison. When the king falls as victim to the succeeding insurrection, the Passio writes that he is killed a militibus suis, by his own warriors. (12) A later work by the Anglo-Saxon cleric Ælnoth (1104-17) says that the ministri regii, the magnates, and the nobiles live on the royal manors, receive the king’s income and fall as victims to the rebels. The magnates and the uulgus of the navy are termed the king’s sui, his ’men’. It is Ælnoth’s ideal that the king takes council with wise and prudent men before serious action, that he musters the navy and that in the end he gives the men home-leave. (13) In his reading of Ælnoth Kristian Erslev (1898) unwittingly builds on Allen when he himself takes Ælnoth’s description of the death of King Canute the Saint as proof of his thesis that the magnates should be described as without any organisational relationship to the king, not even in matters military. Erik Arup (1925) insists that Canute the Saint had no authority over the navy, the leiðangr. When in his charter of May 21 1085 Canute maintains his right to fine any peasant who neglects his military duties, Arup regards this as a presumption on the king’s side. (14) Two Danish kings, Harald Blacktooth (987) and Canute the Saint (1086) fell as victims of popular risings. This is an unquestionable indication of their actual weakness, but it has without due cause been taken as proof of a total lack of any hierarchical organisation behind Late Viking Age royal power. Niels Lund (1996) follows here an unbroken historiographical tradition from C.F. Allen and adds that the demand of Canute the Saint of fines for neglecting expeditio should prove the identity between these military dues and an imposition called nefgiald in the Chronicon Roskildense. However, his arguments are logically incorrect. In case the insurrection against Canute should have its cause in any exactions of fines for neglect of military service it is sufficient to notice that the king himself did not make his appearance at the fleet, letting his men wait and eat those provisions that should have carried them through serious warfare. Canute the Saint died as a weak man indeed. But this does not prove that his rulership was ephemeral or based on a weak and undeveloped institution without the king having organizational bonds to magnates and búendr or formal rights over the military. (15) The ideals of the skaldic court poets for Norway during the eleventh century are the same as those propagated by the early Latin sources for Danish society around AD 1100. And the few instances of Danes mentioned by skalds are within the same vein. The Danish naval levy in the skaldic poem of 1064 is the predecessor of the expeditio AD 1085 of Canute the Saint. Magnates known to us are all in public service, the commoners being the king’s þegnar, the milites sui. The society as viewed by contemporary ideology, Old Norse and Latin, can be regarded as what anthropologists term a mature ’redistributive economic system’, a ’state’ developing out of ’chiefdom’, with personal bonds, political ’friendships’, and ’clienteles’ supplementing a hierarchy of offices. Viking societies were never as thoroughly centralized as the early nineteenth century Zulu-State. They were often in serious danger of becoming as violent and chaotic as present day Congo and Afghanistan. The ideology of court poets and ecclesiastics strove to uphold fecundity and peace so necessary to a warrior society. Translated by Florence Ulsig